Statistical needs for agricultural diversification policies and programmes in the Caribbean - Ramprakash, Deo (Commonwealth Secretariat LondonGB, 1990)
Looks at the agricultural policies and programees of four Caribbean countries viz Grenada, St. Lucia, Trinidad and Tobago and Jamaica. emphasizes the need for statistics to be used for the development of farmers efficiency; better marketing skills and improvement in the estimation of GDP.